Peningkatan Resiliensi Mental Remaja Melalui Modifikasi Latihan Adaptasi: Pendekatan Model Adaptasi Roy - Ike Puspitaningrum; Sukma Diani Putri; Evi Supriatun; Sri Endang Pujiastuti (Jurnal Riset Kesehatan, 2026)
Adolescence and early adulthood are transitional developmental periods characterized by psychological vulnerability, academic stress, and adaptation challenges. Limited evidence exists regarding theory-based resilience interventions that integrate physiological, psychological, and social adaptation processes among nursing students in Indonesia The research aimed to analyze the effectiveness of Roy Adaptation Model-based modified adaptation training in improving mental resilience among first-year nursing students. modified adaptation training consisted of adaptive exercises, autogenic relaxation, and adaptive card games, on the level of mental resilience in adolescents. This study utilized a quantitative approach with a quasi-experimental pre-test–post-test control group design. The research sample comprised 118 (n=59 intervention group, n=59 control group) first-year nursing students enrolled in a health higher education institution in West Java, Indonesia. The intervention group received modified adaptation training over two weeks (60–90 minute sessions), designed based on the four adaptation modes of RAM (physiologic, self-concept, role function, and interdependence). The control group received standard health information booklets. Resilience was measured using the Adolescent Resilience and Adaptation Scale (ARAS). Data were analyzed using non-parametric tests Mann-Whitney U test due to non-normal data distribution. The research findings indicated a significant increase in resilience within the intervention group. The Mann–Whitney U test revealed a significant difference in post-test resilience scores between the groups (U = 719, p < 0.001). The modified adaptation training intervention based on RAM significantly enhanced adolescent mental resilience, offering a theory-based approach with implications for developing intervention programs in school and community settings. The intervention may serve as an evidence-based mental health promotion strategy in educational settings.